A lithium extraction method for recycling positive electrode materials of waste lithium batteries
By combining glucose carbothermal reduction and copper sulfate sulfation roasting, the problem of low lithium recovery rate in lithium battery cathode material recycling has been solved, achieving efficient and environmentally friendly lithium recycling, and is applicable to the recycling of various lithium battery cathode materials.
Patent Information
- Application Number
- CN202611461564.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-11-06
AI Technical Summary
Existing lithium battery cathode material recycling methods have low lithium recovery rates. Traditional methods suffer from problems such as high acid and alkali consumption, large lithium ion loss, complex processes, and environmental unfriendliness.
A method combining glucose carbothermal reduction and copper sulfate sulfation roasting is adopted to convert lithium into soluble salts through two-step roasting. Oxalic acid is used for deep impurity removal, which simplifies the process, reduces the amount of acid and alkali used, and improves the lithium recovery rate.
It improves lithium recovery rate to over 92%, simplifies process flow, reduces acid and alkali usage, and reduces environmental pollution. It is suitable for the recycling of various lithium battery cathode materials such as NCM and LCO.
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery cathode material recycling technology, and in particular to a lithium extraction method for recycling waste lithium battery cathode materials. Background Technology
[0002] Lithium-ion batteries are one of the most commonly used energy storage batteries. In recent years, with the development of the new energy vehicle industry, the demand for lithium batteries has increased rapidly. However, the cost of lithium, the raw material for producing lithium batteries, is high and the mining resources are limited. Extracting lithium from waste lithium batteries not only has high economic value, but can also solve the environmental pollution problem caused by mining.
[0003] Traditional lithium extraction methods for lithium-ion battery cathode materials primarily involve hydrometallurgy, using hydrogen peroxide as a reducing agent and strong acids as leaching agents. This reduces high-valence metals to lower valences and disrupts the stable crystal structure, enabling efficient leaching in acidic solutions. Subsequent extraction and precipitation processes gradually remove other metals, collecting the precipitated lithium. This process is complex, consumes large amounts of acid and alkali, and hydrogen peroxide is volatile and unstable during leaching. The multiple processing steps result in significant lithium-ion loss and low leaching rates. To overcome these shortcomings, a roasting-water leaching method has gained attention. Cathode powder and additives such as sodium sulfate or ammonium sulfate are sulfated and roasted, followed by water leaching to extract lithium into the solution. This significantly reduces acid and alkali consumption. However, using ammonium sulfate as an additive releases NH3 during roasting, corroding equipment. While sodium sulfate does not release corrosive gases, sodium ions enter the leaching solution, making them difficult to remove during subsequent lithium carbonate preparation. This requires multiple deep purification steps, resulting in significant lithium loss and low lithium recovery rates. Summary of the Invention
[0004] The purpose of this invention is to provide a lithium extraction method for recycling cathode materials from waste lithium batteries, which can solve the technical problem of low lithium recovery rate in the prior art.
[0005] The technical problem to be solved by this invention can be achieved through the following technical solution: A method for lithium extraction from recycled cathode materials of waste lithium batteries includes the following steps: Step 1: Obtain cathode powder from waste lithium battery cathode materials through pretreatment; Step 2: Grind and mix the positive electrode powder and glucose, then calcine them once in a muffle furnace under a nitrogen atmosphere; Step 3: After grinding and mixing the primary roasting material and copper sulfate pentahydrate, the mixture is roasted a second time in an air atmosphere in a muffle furnace; Step 4: After soaking the secondary roasted material in water, centrifuge to obtain crude leachate; Step 5: Add oxalic acid to the crude leachate, and centrifuge after acid leaching to obtain lithium-rich leachate; Step 6: Add saturated sodium carbonate solution to the lithium-rich leachate, heat and stir to react and form lithium carbonate precipitate, filter, wash and dry to obtain lithium carbonate.
[0006] This invention optimizes conventional roasting-lithium extraction methods by combining carbothermal reduction, sulfation roasting, and organic acid leaching. This reduces the amount of acid and alkali used while avoiding the introduction of impurity ions and increasing the depth of impurity removal, thereby improving lithium recovery. In this invention, glucose is first ground and mixed with cathode powder as a reducing agent, followed by roasting. The reducing gas from glucose pyrolysis converts insoluble lithium in the cathode powder into soluble lithium, releasing it from the crystal lattice. The cathode powder is then converted into water-soluble lithium carbonate and transition metal oxides. However, during the reduction roasting with glucose and organic matter, excessively high temperatures can cause the reduction products to form alloys of transition metals, while lithium carbonate liquefies and recrystallizes, hindering lithium leaching. Conversely, low temperatures can lead to insufficient thermal reduction, preventing complete conversion of lithium ions into lithium carbonate, which remains in the form of insoluble complex oxides, resulting in low lithium ion recovery. This invention adds sulfation roasting after carbothermal reduction of the cathode powder with glucose, using anhydrous copper sulfate as the sulfate. For ammonium sulfate, pyrolysis does not produce ammonia. During the secondary roasting process, residual lithium ions combine with sulfate ions. Through the combination of the two roasting steps, soluble lithium salts and insoluble transition metal oxides are generated. After roasting, water leaching ensures sufficient leaching of lithium ions. Then, oxalic acid is used as an organic acid for acid leaching, causing the residual transition metals in the leachate to precipitate as oxalates, separating them from the lithium ions. Copper sulfate, as the sulfate introduced during sulfation roasting, partially converts copper ions into insoluble metal oxides. The remaining excess or residual copper sulfate can be separated and removed together with other residual transition metal ions as precipitates during acid leaching. No additional deep impurity removal steps are needed. The loss of lithium during the process is small, and the recovery rate is high. This invention improves the lithium leaching rate by combining glucose carbothermal reduction and copper sulfate sulfation roasting. The overall process is environmentally friendly and controllable, applicable to various systems such as NCM and LCO, and has good industrialization prospects.
[0007] Furthermore, the active component of the waste lithium battery cathode material is at least one of lithium nickel cobalt manganese oxide and lithium cobalt oxide.
[0008] Furthermore, the pretreatment involves removing the current collector by mechanical stripping or heat treatment; The heat treatment conditions are as follows: heating to 450-550℃ under a nitrogen atmosphere and holding for 10-20 minutes.
[0009] PVDF decomposes at 450-550℃, causing the active components to peel off from the aluminum foil without damaging the aluminum foil.
[0010] Furthermore, the mass of the glucose is 10-15% of the mass of the positive electrode powder.
[0011] Furthermore, the primary calcination temperature is 540-580℃, and the holding time is 60-90 minutes. The primary calcination temperature should not be too high, as excessively high temperatures can cause alloys to form between the transition metals, thereby hindering the release of lithium ions.
[0012] Furthermore, the mass ratio of copper sulfate pentahydrate to the primary calcined material is 0.5-0.8:1.
[0013] Furthermore, the secondary calcination temperature is 500-550℃, and the holding time is 40-60 minutes. The secondary calcination temperature should not be too high. Calcination at excessively high temperatures will lead to a decrease in the crystallinity of Li2SO4, and excessive heat energy will interfere with crystal formation. High temperatures will bring higher atomic and molecular kinetic energy, thereby reducing the capture and binding efficiency and hindering the crystallization process.
[0014] Furthermore, the solid-liquid ratio of the water immersion is 100-200 g / L, and the water immersion time is 60-120 min.
[0015] Furthermore, the concentration of oxalic acid used in the acid leaching is 0.2-0.3 mol / L, the acid leaching temperature is 60-90℃, and the acid leaching time is 60-120 min.
[0016] Furthermore, the amount of saturated sodium carbonate solution added satisfies the ratio of the molar amount of carbonate ions to the theoretical molar amount of lithium ions in the cathode powder being 0.6-0.8:1.
[0017] The parameters of each step are optimized in a coordinated manner to ensure that the lithium recovery rate is ≥92% and the impurity metal removal rate is ≥98%.
[0018] The beneficial effects of this invention are: 1. This invention combines two methods—carbothermic reduction of glucose and sulfation roasting of copper sulfate—to synergistically improve lithium recovery. The carbothermic reduction method utilizes the reducing gas generated by glucose pyrolysis to disrupt the crystal structure of the positive electrode active components (such as lithium nickel cobalt manganese oxide and lithium cobalt oxide), releasing lithium ions from the crystal lattice and converting them into water-soluble lithium carbonate. However, when used alone, the temperature window is narrow; excessively high temperatures can lead to transition metal alloying and hinder lithium leaching, while excessively low temperatures result in insufficient reduction, leaving lithium in the form of insoluble complex oxides. This invention introduces a sulfation roasting process, using copper sulfate pentahydrate as the sulfate, and roasting it twice in an air atmosphere. This allows residual lithium ions to detach and combine with sulfate ions to form soluble lithium sulfate. The two roasting steps complement each other: the former completes the initial lithium ion release and conversion, while the latter performs deep sulfation to supplement the conversion, ultimately fully converting lithium into water-soluble salts.
[0019] 2. In this invention, copper sulfate is introduced as the sulfation reagent. During the secondary roasting, some copper ions are converted into insoluble metal oxides, while the excess or residual copper sulfate can precipitate and separate as oxalate along with residual transition metal ions in the leaching solution during the subsequent oxalic acid leaching process. Effective separation of lithium and transition metals can be achieved without additional deep impurity removal processes, resulting in a simple process flow and convenient operation and control.
[0020] 3. Compared to traditional wet leaching processes that require large amounts of inorganic acids (such as sulfuric acid and hydrochloric acid) and alkali solutions for leaching and impurity removal, this invention pre-converts lithium into water-soluble salts through a two-step roasting process. Subsequent water leaching is sufficient to extract the main lithium components. For the small amount of residual transition metals in the leachate, a low-concentration oxalic acid solution is used for acid leaching. The property of oxalic acid to form insoluble oxalate precipitates with transition metal ions is utilized for further separation. Overall, the amount of acid and alkali used is significantly reduced, wastewater discharge pressure is low, and the process is environmentally friendly. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1 Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical stripping to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520°C at a rate of 10°C / min, and calcined at 520°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 98.3% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0023] Example 2 The only difference from Example 1 is that the current collector is removed by heat treatment.
[0024] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected. The aluminum foil current collector was removed through heat treatment: heating to 500℃ under a nitrogen atmosphere and holding for 15 min to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560℃ at a rate of 10℃ / min, and calcined at 560℃ for 75 min. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520℃ at a rate of 10℃ / min, and calcined at 520℃ for 50 min. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 98.1% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0025] Example 3 The only difference from Example 1 is that waste lithium cobalt oxide cathode material is collected for lithium extraction.
[0026] Waste lithium cobalt oxide cathode material was collected, and the aluminum foil current collector was removed by mechanical stripping to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520°C at a rate of 10°C / min, and calcined at 520°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 98.6% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0027] Example 4 The only difference from Example 1 is that the mass of glucose is 10% of the mass of the positive electrode powder.
[0028] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical stripping to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520°C at a rate of 10°C / min, and calcined at 520°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 96.7% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0029] Example 5 The only difference from Example 1 is that the mass of glucose is 15% of the mass of the positive electrode powder.
[0030] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical peeling to obtain cathode powder. The cathode powder was mixed with glucose (15% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520°C at a rate of 10°C / min, and calcined at 520°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 97.8% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0031] Example 6 The only difference from Example 1 is that the mass ratio of copper sulfate pentahydrate to the primary calcined material is 0.5:1.
[0032] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical peeling to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.5, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520°C at a rate of 10°C / min, and calcined at 520°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 97.2% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0033] Example 7 The only difference from Example 1 is that the mass ratio of copper sulfate pentahydrate to the primary calcined material is 0.8:1.
[0034] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical stripping to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.8, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 520°C at a rate of 10°C / min, and calcined at 520°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 98.2% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0035] Example 8 The only difference from Example 1 is that the temperature of the second calcination is 500°C.
[0036] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical peeling to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 500°C at a rate of 10°C / min, and calcined at 500°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 97.4% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0037] Example 9 The only difference from Example 1 is that the temperature of the second calcination is 550°C.
[0038] Waste lithium nickel cobalt manganese oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical peeling to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 550°C at a rate of 10°C / min, and calcined at 550°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 97.9% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0039] Comparative Example 1 The only difference from Example 1 is that only glucose is used for carbothermal reduction roasting.
[0040] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical stripping to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560℃ at a rate of 10℃ / min, and calcined at 560℃ for 75 min. After calcination, the muffle furnace was turned off, and the calcined product was allowed to cool to room temperature. The calcined material was then mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40℃. After leaching, the mixture was centrifuged to obtain crude leachate. Oxalic acid was added to the crude leachate, controlling the oxalic acid concentration at 0.25 mol / L, and acid leaching was performed at 75℃ for 90 min. After acid leaching, the mixture was centrifuged to obtain lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added such that the molar ratio of carbonate ions to the theoretical molar ratio of lithium ions in the cathode powder was 0.7:1. The mixture was stirred at 95°C for 2 hours to form a precipitate, which was then filtered, washed with deionized water, and vacuum dried at 80°C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment was found to be 92.5% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in the cathode powder × 100%).
[0041] Comparative Example 2 The only difference from Example 1 is that the temperature of glucose carbothermal reduction roasting is increased, and secondary roasting is not performed.
[0042] Waste nickel-cobalt-manganese lithium oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical stripping to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 600℃ at a rate of 10℃ / min, and calcined at 600℃ for 75 min. After the first calcination, the muffle furnace was turned off, and the calcined product was allowed to cool to room temperature. The calcined material was then mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40℃. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, controlling the oxalic acid concentration at 0.25 mol / L, and acid leaching was performed at 75℃ for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added such that the molar ratio of carbonate ions to the theoretical molar ratio of lithium ions in the cathode powder was 0.7:1. The mixture was stirred at 95°C for 2 hours to form a precipitate, which was then filtered, washed with deionized water, and vacuum dried at 80°C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment was found to be 93.4% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in the cathode powder × 100%).
[0043] Comparative Example 3 The only difference from Example 1 is that the temperature of the second firing is increased to 570°C.
[0044] Waste lithium nickel cobalt manganese oxide (NCM523 type) ternary cathode material was collected, and the aluminum foil current collector was removed by mechanical peeling to obtain cathode powder. The cathode powder was mixed with glucose (12% of the cathode powder mass), ground uniformly, and then placed in a muffle furnace. Under a nitrogen atmosphere, the temperature was increased to 560°C at a rate of 10°C / min, and calcined at 560°C for 75 minutes. After the first calcination, the muffle furnace was closed, and the calcined product was allowed to cool to room temperature. It was then mixed with copper sulfate pentahydrate at a mass ratio of 1:0.6, ground uniformly, and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 570°C at a rate of 10°C / min, and calcined at 570°C for 50 minutes. After the second calcination, the calcined product was allowed to cool naturally to room temperature. The secondary roasted material was mixed with water at a solid-liquid ratio of 150 g / L and stirred at 300 r / min for 90 min at 40 °C. After leaching, the mixture was centrifuged to obtain a crude leachate. Oxalic acid was added to the crude leachate, with the concentration controlled at 0.25 mol / L. The mixture was then acid-leached at 75 °C for 90 min. After acid leaching, the mixture was centrifuged to obtain a lithium-rich leachate. A saturated sodium carbonate solution was added to the lithium-rich leachate, with the amount of saturated sodium carbonate solution added ensuring a molar ratio of carbonate ions to theoretical lithium ions in the cathode powder of 0.7:1. The mixture was stirred at 95 °C for 2 h to form a precipitate. After filtration, the precipitate was washed with deionized water and vacuum-dried at 80 °C to constant weight to obtain lithium carbonate. The lithium recovery rate in this embodiment reached 95.6% (lithium recovery rate = mass of lithium in lithium carbonate / mass of theoretical lithium in cathode powder × 100%).
[0045] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for lithium extraction from recycled cathode materials of waste lithium batteries, characterized in that, Includes the following steps: Step 1: Obtain cathode powder from waste lithium battery cathode materials through pretreatment; Step 2: Grind and mix the positive electrode powder and glucose, then calcine them once in a muffle furnace under a nitrogen atmosphere; Step 3: After grinding and mixing the primary roasting material and copper sulfate pentahydrate, the mixture is roasted a second time in an air atmosphere in a muffle furnace; Step 4: After soaking the secondary roasted material in water, centrifuge to obtain crude leachate; Step 5: Add oxalic acid to the crude leachate, and centrifuge after acid leaching to obtain lithium-rich leachate; Step 6: Add saturated sodium carbonate solution to the lithium-rich leachate, heat and stir to react and form lithium carbonate precipitate, filter, wash and dry to obtain lithium carbonate.
2. The lithium extraction method for recycling waste lithium battery cathode materials according to claim 1, characterized in that, The active component of the spent lithium battery cathode material is at least one of lithium nickel cobalt manganese oxide and lithium cobalt oxide.
3. The lithium extraction method for recycling waste lithium battery cathode materials according to claim 1, characterized in that, The pretreatment involves removing the current collector by mechanical stripping or heat treatment; The heat treatment conditions are as follows: heating to 450-550℃ under a nitrogen atmosphere and holding for 10-20 minutes.
4. The lithium extraction method for recycling waste lithium battery cathode materials according to claim 1, characterized in that, The glucose content is 10-15% of the mass of the positive electrode powder.
5. A method for lithium extraction from recycled cathode materials of waste lithium batteries according to claim 1, characterized in that, The temperature of the first roasting is 540-580℃, and the holding time is 60-90 minutes.
6. The lithium extraction method for recycling waste lithium battery cathode materials according to claim 1, characterized in that, The mass ratio of copper sulfate pentahydrate to the primary roasting material is 0.5-0.8:
1.
7. A method for lithium extraction from recycled cathode materials of waste lithium batteries according to claim 1, characterized in that, The secondary roasting temperature is 500-550℃, and the holding time is 40-60 minutes.
8. A method for lithium extraction from recycled cathode materials of waste lithium batteries according to claim 1, characterized in that, The solid-liquid ratio of the water immersion is 100-200 g / L, and the immersion time is 60-120 min.
9. A method for lithium extraction from recycled cathode materials of waste lithium batteries according to claim 1, characterized in that, The concentration of oxalic acid used in the acid leaching is 0.2-0.3 mol / L, the acid leaching temperature is 60-90℃, and the acid leaching time is 60-120 min.
10. A method for lithium extraction from recycled cathode materials of waste lithium batteries according to claim 1, characterized in that, The amount of saturated sodium carbonate solution added satisfies the ratio of the molar amount of carbonate ions to the theoretical molar amount of lithium ions in the cathode powder of 0.6-0.8:1.
